2022
DOI: 10.3389/fvets.2022.903890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immune responses to Brucella vaccines in mouse models: A systematic review

Abstract: IntroductionDespite the accessibility of several live attenuated vaccines for animals, currently, there is no licensed vaccine for brucellosis in human populations. Available and confirmed animal vaccines may be harmful and considered inappropriate for humans. Thus, human vaccines for brucellosis are required. We aimed to evaluate the effects of Brucella vaccines on mouse models and discuss the potential mechanisms of these vaccines for the design of the appropriate human vaccines.Materials and methodsA system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Despite the lack of a safe and effective Brucella vaccine for humans, animal vaccinations are essential not only to safeguard animal health, but also to prevent the spreading of diseases transmitted from animals to humans. Several drawbacks of these vaccines have been reported by Darbandi et al [ 157 ]. Among these are: (i) they remain virulent in humans; (ii) they cause abortion in pregnant animals; (iii) it can be difficult to differentiate between infected and vaccinated animals due to the persistent serological response they induce; (iv) they are relatively unstable.…”
Section: Brucella Vaccine Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lack of a safe and effective Brucella vaccine for humans, animal vaccinations are essential not only to safeguard animal health, but also to prevent the spreading of diseases transmitted from animals to humans. Several drawbacks of these vaccines have been reported by Darbandi et al [ 157 ]. Among these are: (i) they remain virulent in humans; (ii) they cause abortion in pregnant animals; (iii) it can be difficult to differentiate between infected and vaccinated animals due to the persistent serological response they induce; (iv) they are relatively unstable.…”
Section: Brucella Vaccine Developmentmentioning
confidence: 99%
“…DNA vaccines are suitable for diseases that require cellular immunity. Human studies have shown that these vaccines induce weaker immune responses than mice; therefore, they need to be optimized [ 157 ]. Optimization, however, increases pro-inflammatory reactions [ 178 ].…”
Section: Brucella Vaccine Developmentmentioning
confidence: 99%
“…To ascertain its effectiveness for vaccination, the IP route was selected since it better mimics disease outcome resulting in a systemic disease [ 6 , 7 ]. Moreover, IP vaccination has proven effective in experimental models in conferring protection and significant brucellae clearance [ 41 ]. A limitation with conventional Brucella vaccines lies in their incomplete efficacy, providing only about 70% efficacy against wt Brucella abortion challenges [ 11 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effective treatments for animal brucellosis and the high cost of treating infected humans ( 5 , 12 ) emphasize the necessity for robust disease prevention. Current vaccines such as S19, RB51, and Rev1 exhibit around 70% efficacy against animal brucellosis ( 13 15 ), underscoring the need for further research on vaccine-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%